PENGARUH METODE RESITASI DALAM PEMBELAJARAN SOSIOLOGI TERHADAP HASIL BELAJAR SISWA DI KELAS X SMA NEGERI 1 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Fitri, Meliya - (Pendidikan Sosiologi, 2014)
This research is motivated by the low learning outcomes Sociology Students of class X SMA N 1 beheaded Problem academic year 2013/2014. This is due to the many students dont pay attention to the learning activities when teachers explain the learning materials. The problem in this study is